Strategies To Improve The Quality Of Learning Towards Critical Thinking Skills In Students Of Smp Negeri 24 Makassar - Andi Tenri Ampa; Andi Annisa Sulolipu; Andi Tonra Lipu (International Journal of Education, Vocational and Social Science, 2025)
This study aims to explore learning strategies that can improve the quality of the learning process in order to develop critical thinking skills in students. Using a qualitative approach, this study was conducted through observation, in-depth interviews, and documentation studies of teachers and students at the secondary school level. The main focus of the study was the identification of effective pedagogical practices, as well as supporting and inhibiting factors in implementing these strategies in the classroom. The results of the study indicate that the implementation of active learning strategies such as group discussions, problem-based learning, and the use of open-ended questions consistently can increase student engagement and encourage them to think critically. In addition, the role of teachers as facilitators and creators of learning environments that support open dialogue is the key to success in this process. This study recommends professional development for teachers in designing learning strategies that emphasize strengthening students' critical thinking skills.